The co-developmental dynamic of sport and school burnout among student-athletes: The role of achievement goals - Sorkkila, M.; Aunola, K.; Salmela-Aro, K.; Tolvanen, A.; Ryba, T. V. (Scandinavian Journal of Medicine & Science in Sports, 2018)
Student-athletes who strive for success in high-level sports while pursuing upper secondary education may be prone to sport and school burnout. This study examined the co-developmental dynamic of sport and school burnout in Finnish adolescent student-athletes (Ntime 1 = 391; Ntime 2 = 373) across the first year of upper secondary school using cross-lagged structural equation modeling (SEM). Furthermore, we used sport and school-related achievement goals as predictors of sport and school burnout, namely sport and school-related exhaustion, cynicism, and feelings of inadequacy. The results showed that burnout dimensions in a particular domain were substantially stable within the same domain during the first year of upper secondary school and that school-related exhaustion at the beginning of upper secondary school predicted sport-related exhaustion at the end of the school year. Mastery goals in sport and school were negatively associated with cynicism and feelings of inadequacy within the same domain. Furthermore, performance goals in school were positively associated with school-related cynicism. The results can be used by healthcare professionals for early prevention of student-athletes' burnout.